Pomegranate Cultivation Techniques: Maximizing Yield (Journal of Universal Science Research, 2023)
This article delves into the art of successful pomegranate cultivation, exploring key techniques to maximize yields and fruit quality. From selecting the right variety and preparing the soil to pest management and post-harvest handling, it provides a comprehensive guide for both novice gardeners and experienced growers. Additionally, it emphasizes sustainability, adaptation to local climates, and community engagement for a well-rounded approach to pomegranate farming.